2015
DOI: 10.1017/s2040174415007825
|View full text |Cite
|
Sign up to set email alerts
|

Adult male mice conceived byin vitrofertilization exhibit increased glucocorticoid receptor expression in fat tissue

Abstract: Prenatal development is highly plastic and readily influenced by the environment. Adverse conditions have been shown to alter organ development and predispose offspring to chronic diseases, including diabetes and hypertension. Notably, it appears that the changes in glucocorticoid hormones or glucocorticoid receptor (GR) levels in peripheral tissues could play a role in the development of chronic diseases. We have previously demonstrated that in vitro fertilization (IVF) and preimplantation embryo culture is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…In the current study, Txnip is upregulated in all ART blastocysts except for the ICSI and the IVC – KAA 20% oxygen conditions. In another study we reported that glucocorticoid receptor (GR) expression is increased in IVF – KAA 5% O 2 embryos and male offspring fat, but not liver or muscle (Simbulan, et al 2015). …”
Section: Discussionmentioning
confidence: 98%
“…In the current study, Txnip is upregulated in all ART blastocysts except for the ICSI and the IVC – KAA 20% oxygen conditions. In another study we reported that glucocorticoid receptor (GR) expression is increased in IVF – KAA 5% O 2 embryos and male offspring fat, but not liver or muscle (Simbulan, et al 2015). …”
Section: Discussionmentioning
confidence: 98%
“…In another study, increased glucocorticoid receptor (GR) expression was observed in inbred and outbred mouse IVP blastocysts cultured in KSOM. Subsequently, although the plasma corticosterone concentrations were unchanged, a sex‐specific increase in GR gene and protein expression was observed in the fat of adult male offspring (Simbulan et al, ). Interestingly, the increased GR reported in blastocysts was not associated with differential expression in any tissue in adults when embryos were incubated in Whittens' medium, highlighting the high specificity of the response depending on the culture medium (Simbulan et al, ).…”
Section: Long‐term Effects Of Artmentioning
confidence: 99%
“…Interestingly, both male and female IVF KAA mice retain fatexclusive maintenance of transcriptional changes present in IVF blastocysts compared with other adult tissues, including increased expression of the GR 45 and thioredoxin-interacting protein (Txnip, discussed below). 3 These data suggest that adipose tissue may be a locus of sex-and tissue-specific changes associated with IVF.…”
Section: Adipose Tissuementioning
confidence: 99%
“…58 We have investigated this hypothesis in the mouse by analyzing two candidate genes that demonstrate significant blastocyst transcriptional modification after in vitro exposure compared with control embryos: Txnip and the GR Nr3c1. 3,45 We selected Txnip because the literature suggested it might function as a sensitive marker of preimplantation stress. TXNIP operates at the intersection of multiple cellular stress, redox and metabolic pathways: it is the principal inhibitor of the antioxidant thioredoxin; it regulates the PI3K/AKT pathway and is involved in peripheral glucose homeostasis; it regulates β-cell mass by decreasing mitochondrial apoptosis.…”
Section: Master Regulator Gene Hypothesismentioning
confidence: 99%